Pengelolaan Pariwisata Bahari berbasis Community-Based Tourism dalam Peningkatan Ekonomi Masyarakat Pesisir - Rullyana Puspitaningrum Mamengko; Erlina Daru Kuntari (Media Wisata, 2020)
This study aimed to determine the importance of community-based tourism management in increasing the economic income of coastal communities in the coastal areas of the North Coast of Central Java. This research was funded by the Directorate of Research and Community Service (DRPM) of the Ministry of Research, Technology and Higher Education. This research is a qualitative descriptive study with research procedures, namely the description stage, the reduction stage, and the selection stage. The research location is in the coastal area of the North Coast of Central Java with randomly selected respondents. The results obtained are the multiplayer effect of community involvement in marine tourism management in coastal areas, including increased community income, absorption of local workers, the opening of business space for local communities, maintaining the surrounding environment, and improving other supporting amenities.